Cryptogenic recurrent spontaneous intracranial epidural hematoma: A case report and literature review - Xu, Min; Xue, Ya; Chao, Xiaofeng; Chen, Zhenglou; Wang, Yunjiang; Huo, Xuqi; Ji, Xiang; Wang, Hongshen (Frontiers in Neurology, 2023)
Background: Spontaneous epidural hematoma (EDH) has been suggested associated with adjacent infective pathologies, dural vascular malformations, extradural metastasis, or coagulopathies. Cryptogenic spontaneous EDH is extremely rare. Case presentation: We reported a cryptogenic spontaneous EDH case in a young woman following sexual intercourse. She occurred consecutively EDH at three different sites within a short time. After three timely operations, a satisfactory outcome was achieved. Conclusion: EDH should be investigated when a young patient develops headaches and signs of increased ICP after emotional hyperactivity or hyperventilation. If early diagnosis and surgical decompression can be carried out in time, the prognosis is satisfactory.